Young people's views of UK mental health services - Plaistow, J; Masson, K; Koch, D; Wilson, J; Stark, R; Jones, P; Lennox, B (Blackwell Publishing, 2014)
Aims and method: Adolescence is the period of highest risk for the development of mental illness, but also the age group least likely to seek help from mental health services. We undertook a systematic review of the published literature on the views of young people of mental health services in the UK and a thematic analysis of the findings to explore the reasons behind this to guide those developing services for young people. Results: Thirty-one studies were identified, which captured the views of 13605 young people including 625 young people who had experience of mental health services. Positive views to emerge were of qualities of mental health workers and encouraging self-reliance. Negative views were of stigma, lack of information, medicalization of their problems and a lack of continuity of care. Conclusions: Young people have consistent views of the positive and negative aspects of mental health services, which could be helpfully incorporated in the design of services. The views of some groups of young people have not been well represented, however, and the views of minority ethnic groups and those who have disengaged from services in particular need to be actively sought. © 2013 Wiley Publishing Asia Pty Ltd.